A Chinese strategy to construct a comprehensive investigation system for hadal trenches. (September 2018) - Cui, Weicheng; Wu, Xin
Abstract: Human curiosity for the natural world is the leading factor for the progress in deep ocean exploration. However, only in the last 60 years has the technological capability satisfied the human desire to reach the deepest point of the oceans. In this paper, the history of human exploration to the deep oceans is reviewed with a focus on the lessons learned from these pioneers. From this review, it is shown that deep-sea trenches remain one of the least explored ocean ecosystems due to a wide range of issues such as lack of investigation platforms and cruise funding. Although humans have twice reached the deepest point of the oceans, up to now there were no operational platforms for ocean scientists to freely conduct scientific research in hadal trenches. Therefore, a new strategy is being introduced in China to overcome the technical and funding issues to develop a comprehensive investigation system for hadal trenches. Through more than four years' practice, the new strategy has proved to be effective and the first phase of the comprehensive investigation system has been constructed. In this paper, this new strategy and its progress are presented and the underlying philosophy is explained.